Partial Discharge Detection using Rogowski Coil Sensor on Medium Voltage Aerial Bundle Cable - N. Rameli; H. S. A. Halim; M. I. Nor Azli; T.Marie Anthony; M. A. Pangah@Pa’at; M. F. Ibrahim; N. A. Arifin (UiTM Press, 2024)
JOURNAL OF ELECTRICAL AND ELECTRONIC SYSTEMS RESEARCH, VOL17 DEC 2020